A comparative study for production of germ tube in Candida albicans of various pulmonary samples, by different methods in a tertiary care hospital of south west Rajasthan - Bhumbla, Upasana; Gupta, Amit (International Journal Of Community Medicine And Public Health, 2021)
Background: Systemic candidiasis is associated with a high crude mortality rate, even with first line antifungal therapy. C. albicans is the predominant cause of invasive fungal diseases which is a serious public health issue. The main objective was to assess the reliability of different media for germ tube production in Candida albicans isolated from various clinically diagnosed pulmonary samples. Methods: All Candida isolates were identified and speciated by conventional methods such as Gram’s staining, germ tube test, chlamydospore formation on corn meal agar, sugar fermentation test, sugar assimilation test, and growth on Hi-chrome candida agar. Results: Out of 108 clinical isolates of Candida albicans, 5 different methods were used for germ tube production. Pooled human sera showed 93/108 (86.1%) was the most sensitive method wherein YEPD (yeast extract peptone dextrose) broth 91/108 (84.7%) was the reliable and easy method for detection of germ tube, followed by trypticase soy broth 81/108 (81.4%); peptone water 80/108 (74.7%) and 2% sucrose 71/108 (65.7%). Conclusions: YPED broth is found to be a better serum free substrate and subsequently for the presumptive differentiation of C. albicans from non-albicans candida (NAC), without the extensive time required for the preparation and testing of pooled human serum. Furthermore, this medium is commercially available, more stable, effective, and is not bio hazardous.